Health-Related Quality of Life (HRQoL) Assessments in Research on Patients with Adult Rare Solid Cancers: A State-of-the-Art Review - Padilla, Catarina S; Bergerot, Cristiane D; Dijke, Kim; Roets, Evelyne; Boková, Gabriela; Innerhofer, Veronika; Sodergren, Samantha C; Mancari, Rosanna; Bergamini, Cristiana; Way, Kirsty M; Sapoznikov, Olga; Burgers, Jacobus A; et al. (Cancers, 2025)
BACKGROUND: Health-related quality of life (HRQoL) is an important patient-reported outcome for all cancer patients, including adult patients with rare solid cancers. However, current knowledge of HRQoL in this population is limited, which hinders the delivery of personalized care. This review aimed to explore the heterogeneity of HRQoL among adult patients with a solid rare cancer across the ten European Reference Network for Rare Adult Solid Cancers (EURACAN) domains and to summarize the HRQoL measures used in clinical research. METHODS: A systematic literature search was conducted to identify all clinical studies assessing HRQoL in adult patients with a solid rare cancer. Four databases (MEDLINE, PubMed, PsycINFO, and Web of Science/Scopus) were searched (February 2023). RESULTS: The search yielded 18,704 articles, of which 1416 articles were fully screened and 463 were eligible for analysis. Of these, 397 studies used generic tools to assess HRQoL, while 270 used tumor-specific instruments. Three EURACAN domains (sarcoma, endocrine tumors, and thoracic tumors) primarily assessed HRQoL using generic questionnaires. Additionally, the rare gynecological tumor, rare male genitourinary, and sarcoma EURACAN domains lacked specific HRQoL measures. Brain, head and neck, and uveal melanoma EURACAN domains used tumor- or domain-specific questionnaires in more than half of the studies. CONCLUSIONS: This state-of-the-art literature review shows that HRQoL assessment is gradually becoming more prevalent in adult solid rare cancer research. A combination of generic, tumor-specific, and domain-specific questionnaires across various rare cancer domains has proven effective in capturing a broad range of HRQoL issues. However, many EURACAN domains still lack specific strategies for assessing HRQoL, which limits the ability to fully understand and address patients' experiences. Future research should prioritize developing comprehensive and robust HRQoL measurement strategies and tools to enable meaningful clinical research and to ensure that the patient voice is incorporated in their clinical care.
Keywords: health-related quality of life; EURACAN; adult rare solid cancers; systematic review